Driving justice, equity, diversity, and inclusion - Kohl, Kristina (CRC Press, 2022)
520 "Navigating the volatility, uncertainty, complexity and ambiguity (VUCA) characterizing the business world in the 21st century requires a new paradigm focused on an integrated bottom line-planet, people, profit. Issues include global mega trends, stakeholder demands, resource scarcity, and systemic barriers. Transformational change requires leadership to analyze internal and external systems through a social and environmental justice lens. Despite a growing focus on justice, diversity, equality, and inclusion (JEDI), the imbalance of power remains and manifests itself across organizations. To move the needle, managers can turn to Driving Justice, Equality, Diversity, and Inclusion: The JEDI Journey, which explains redesigning organizational process and systems as well as leveraging tools for data-driven decision-making. It presents a framework to build an inclusive organization as well as a model to engage and support senior and middle management beginning the process of capacity building and systemic change. By layering in AI and other technologies to support data-based decisions, the book shows managers how to move forward in creating just and equitable organizations. The book also helps managers to: Assess ecosystem and organizational systems JEDI impacts. Take a deeper dive into transformational and operational components to gain insights on the deep systemic realignment of the JEDI journey. Identify and engage with diverse stakeholders to gain perspective and understand issues crucial for transformative change. Leverage People- Centered Design to create a process promoting diversity of voices and to better align outcomes with shared organizational vision. To use data to drive decision- making and reduce bias by removing intuition from the decision-making process. The book features a JEDI Primer, which is a quick reference guide to key terms, concepts, and definitions. It helps to define justice, equity, diversity, and inclusion and other key terms such as unconscious bias, stereotypes, and microaggressions. Another feature is the JEDI Toolkit, which includes checklists to help managers lead organizations on the JEDI journey"